The Effects of Transforming Growth Factor-β2 on the Expression of Follistatin and Activin A in Normal and Glaucomatous Human Trabecular Meshwork Cells and Tissues - Fitzgerald, Ashley M. (The Association for Research in Vision and Ophthalmology, 2012)
PURPOSE. To compare follistatin (FST) and activin (Act) expression in normal and glaucomatous trabecular meshwork (TM) cells and tissues and determine if exogenous TGF-β2 regulates the expression of FST and Act in TM cells. METHODS. Total RNA was isolated from TM cell strains, and mRNA expression for FST 317/344 isoforms and Act was determined via RT-PCR and quantitative PCR (qPCR). Western immunoblotting and immunocytochemistry determined FST and Act A protein levels in normal TM (NTM) and glaucomatous TM (GTM) cells. Cells were treated with recombinant human TGF-β2 protein at 0 to 10 ng/mL for 0 to 72 hours. qPCR, Western immunoblotting, immunocytochemistry, and ELISA immunoassay were utilized to determine changes in FST and Act A mRNA and protein levels. In addition, NTM and GTM tissue samples were examined by immunohistochemistry for expression of FST, FST 315, FST 288, and Act A. RESULTS. Both FST mRNA and protein levels were significantly elevated in GTM cells. FST mRNA transcripts FST 317/344 were also significantly elevated in GTM cells. Immunohistochemistry showed FST levels were significantly elevated in GTM tissues. Exogenous TGF-β2 significantly induced FST mRNA and protein expression. Immunohistochemistry demonstrated that Act A protein levels were significantly higher in NTM tissues compared to GTM tissues. CONCLUSIONS. FST is elevated in GTM cells and tissues. FST is known to be an inhibitor of bone morphogenetic proteins (BMPs), which, coupled with the ability of TGF-β2 to upregulate FST levels, may indicate a possible role of FST in the pathogenesis of glaucoma. These results suggest that additional endogenous molecules in human TM may regulate TGF-β2 signaling via inhibition of BMP family members.